Research Trends and Developments in Management Accounting: A Bibliometric Analysis - Tocev, Todor; Trpeska, Marina (My University, 2024)
Purpose Management accounting, as a critical area within the broader domain of accounting, has undergone significant transformations over the years, driven by changes in business practices, technological advancements, and regulatory environments (Merigó and Yang, 2016; Cortés-Sánchez, 2019; Balstad and Berg, 2020). This study aims to identify key themes, influential authors/publications, and emerging research areas that have shaped the field through bibliometric analysis. By examining the evolution of research in management accounting, this study seeks to provide insights into the current state of the field and its future directions. Design/methodology/approach This bibliometric analysis utilized data from the Scopus database, with the search focusing on the keywords "Management" OR "Managerial" AND "Accounting". The initial search identified 66,822 manuscripts. To ensure the relevance and quality of the dataset, the PRISMA protocol was applied through its four stages: identification, screening, eligibility, and inclusion (Moher et al., 2009). Filtering criteria included the subject area of Business Management and Accounting, English language, and document type restricted to articles, which narrowed the dataset to 13,078 papers. After removing duplicates, a manual relevance check based on abstract analysis further reduced the dataset, resulting in a final set of 5,059 papers for the bibliometric analysis. The VOSviewer software was used to analyze co-authorship patterns among authors, organizations, and countries, as well as to perform keyword analysis on abstracts for the entire period and specifically for the last five years (2019-2023). Findings The dataset spans research papers from 1957 to 2023, with a noticeable increase in publications over time, particularly in recent decades. The trend culminated in 2023 with a peak of 354 papers. The most cited individual authors are Kaplan R.S., Norton D.P., Orlitzky M., Schmidt F.L., and Rynes S.L. Some of the leading journals for management accounting publications are "Accounting, Organizations and Society", "Management Accounting Research", "Accounting, Auditing, and Accountability Journal", "Journal of Cleaner Production", and "European Accounting Review". The United States and the United Kingdom rank as the top countries in the total number of published articles and citations. The analysis reveals that the most prominent research themes, based on keyword occurrences, are performance measurement, cost management, financial management, management control systems, and sustainability. These results align with Balstad and Berg's (2020) and Porporato and Werbin's (2024) findings and insights. Originality/value This study employs bibliometric analysis to offer an overview of the evolving field of management accounting. It provides valuable insights into research trends, influential authors, and key publications that have shaped the discipline over the past several decades. The findings deepen the understanding of the intellectual foundation of management accounting, guiding future research and aiding academics and practitioners in navigating the complexities of this field.
Keywords: Management accounting; Bibliometric analysis; Research trends